-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathmath2101-hw1-rjw.tex
346 lines (336 loc) · 15.8 KB
/
math2101-hw1-rjw.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
\documentclass{letter}
\usepackage{enumitem}
\usepackage{mathtools}
\usepackage{fancyhdr}
\usepackage{xcolor}
\usepackage{mdframed}
\usepackage{bm}
\usepackage[letterpaper,portrait,left=2cm,right=2cm,top=3.5cm,bottom=2cm]{geometry}
\pagestyle{fancy}
\fancyhf{}
\rhead{Robert Wagner\\June 9, 2016}
\lhead{Math 2101\\Assignment 1}
\newcounter{question}
\setcounter{question}{0}
\usepackage{amsmath,amsthm}
\usepackage{amssymb}
% magnitude bars
\newcommand{\norm}[1]{\lvert #1 \rvert}
% explicit vector
\newcommand{\Ve}[1]{\langle #1 \rangle}
% named vector
\newcommand{\Vn}[1]{\vec{\bm{#1}}}
\newcommand\Que[1]{%
\leavevmode\noindent
#1
}
\newcommand\Ans[2][]{%
\leavevmode\noindent
{
\begin{mdframed}[backgroundcolor=blue!10]
#2
\end{mdframed}
}
}
\newenvironment{salign}
{\par$\!\aligned}
{\endaligned$\par}
\begin{document}
\begin{enumerate}
\item In the following, let $\Vn{v_1} = \Ve{3, -2, -1}$, $\Vn{v_2} = \Ve{1, 1, -1}$, and $\Vn{v_3} = \Ve{-3, 2, 6}$ be vectors in $\mathbb{R}^3$.\\
Find the following, if possible. If not possible, explain why.
\begin{enumerate}[label=(\alph*)]
\item\Que{$3 \Vn{v_1} - 2 \Vn{v_2} + 4 \Vn{v_3}$}
\Ans{\begin{salign}
3 \Vn{v_1} - 2 \Vn{v_2} + 4 \Vn{v_3} & =
\Ve{ 3 \times 3, 3 \times -2, 3 \times -1 } + \Ve{ -2 \times 1,-2 \times 1,-2 \times -1 } + \Ve{ 4 \times -3, 4 \times 2, 4 \times 6 } \\
& = \Ve{ 9-2-12,-6-2+8, -3-2+24 } \\
& = \underline{\Ve{ -5,0,19 }}
\end{salign}
}
\item \Que{$ \Vn{v_1} \cdot \Vn{v_2}$}
\Ans{\begin{salign}
\Vn{v_1} \cdot \Vn{v_2} &=
(3 \times 1) + (-2 \times 1) + (-1 \times -1) \\
& = 3-2+1 \\
& = \underline{2}
\end{salign}
%[Since $\Vn{v_1} \cdot \Vn{v_2} = 0$, we can see that $\Vn{v_1}$ and $\Vn{v_2}$ are orthogonal.]
}
\item \Que{$ 2 \Vn{v_1} \cdot \Vn{v_2} + 2 \Vn{v_3}$}
\Ans{
This is not possible as written, as evaluating the dot product $2 \Vn{v_1} \cdot \Vn{v_2}$ results in a scalar, and the subsequent addition of the scalar $2 \Vn{v_1} \cdot \Vn{v_2}$ and the vector $2 \Vn{v_3}$ is not defined. However, if it were written
$ 2 \Vn{v_1} \cdot (\Vn{v_2} + 2 \Vn{v_3}) $ then it would evaluate to a scalar.
}
\item \Que{$\Vn{v_1} \cdot \Vn{v_2} \cdot \Vn{v_3} $}
\Ans{
This is not possible as written, as evaluating the dot product $\Vn{v_1} \cdot \Vn{v_2}$ results in a scalar, and the subsequent dot product between the scalar $\Vn{v_1} \cdot \Vn{v_2}$ and the vector $\Vn{v_3}$ is undefined.
}
\item \Que{$\Vn{v_1} \cdot (3 \Vn{v_2} - 2 \Vn{v_3})$}
\Ans{\begin{salign}
\Vn{v_1} \cdot (3 \Vn{v_2} - 2 \Vn{v_3}) {}&=
\Ve{ 3,-2,-1 } \cdot (\Ve{ 3 \times 1, 3 \times 1,
3 \times -1 } + \Ve{ -2 \times -3,
-2 \times 2, -2 \times 6 })\\
&= \Ve{ 3,-2,-1 } \cdot \Ve{ 3 + 6, 3 - 4, -3 - 12 } \\
&= \Ve{ 3,-2,-1 } \cdot \Ve{ 9, -1, -15 } \\
&= (3 \times 9)+(-2 \times -1)+(-1 \times -15) \\
&= 27+2+15 \\
&= \underline{44}
\end{salign}
}
\item \Que{$\norm{\Vn{v_1}}$}
\Ans{\begin{salign}
\norm{\Vn{v_1}} {}&= \norm{\Ve{ 3, -2, -1 }} \\
& = \sqrt{3^2 + (-2)^2 + (-1)^2} \\
&= \sqrt{9 + 4 + 1} \\
&= \underline{\sqrt{14}}
\end{salign}
}
\item \Que{$\norm{5\Vn{v_1}}$}
\Ans{\begin{salign}
\norm{5\Vn{v_1}} {}& = \norm{\Ve{ 5 \times 3, 5 \times -2, 5 \times -1 }} \\
& = \norm{\Ve{ 15, -10, -5 }} \\
& = \sqrt{15^2 + (-10)^2 + (-5)^2} \\
& = \sqrt{225 + 100 + 25} \\
& = \sqrt{350} \\
& = \underline{5\sqrt{14}}
\end{salign}
%[Therefore, it appears that $\norm{5\Vn{v_1}} = 5\norm{\Vn{v_1}}$]
}
\end{enumerate}
\newpage
\item In the following, assume $\Vn{u} = \Ve{ u_1, u_2, u_3 }$ and $\Vn{v}=\Ve{ v_1, v_2, v_3 }$, and $\theta$ is the angle between $\Vn{u}$ and $\Vn{v}$.
\begin{enumerate}[label=(\alph*)]
\item \Que{Prove: $\Vn{u} \cdot \Vn{v} = \norm{\Vn{u}}\norm{\Vn{v}}\cos{\theta}$}
\Ans{Let $\Vn{u}, \Vn{v}$ be non-zero vectors in $\mathbb{R}^3$ such that $\theta \in [0,\pi)$ is the angle between them. The law of cosines states that
\begin{align*}
\norm{\Vn{u} - \Vn{v}}^2 &= \norm{\Vn{u}}^2 + \norm{\Vn{v}}^2 - 2 \norm{\Vn{u}}\norm{\Vn{v}}\cos{\theta}
\shortintertext{is true for all non-zero vectors. Thus}
\norm{\Vn{u} - \Vn{v}}^2 {}&= \norm{\Ve{ u_1-v_1,u_2-v_2,u_3-v_3}}^2 \\
& = (\sqrt{(u_1-v_1)^2+(u_2-v_2)^2+(u_3-v_3)^2})^2 \\
& = (u_1^2-2u_1v_1+v_1^2)+(u_2^2-2u_2v_2 + v_2^2)+(u_3^2-2u_3v_3+v_3^2) \\
& = (\sqrt{u_1^2+u_2^2+u_3^2})^2+(\sqrt{v_1^2+v_2^2+v_3^2})^2 - 2(u_1v_1+u_2v_2+u_3v_3)\\
& = \norm{\Vn{u}}^2 + \norm{\Vn{v}}^2 - 2(\Vn{u} \cdot \Vn{v})
\shortintertext{and we can rewrite the law of cosines as}
\norm{\Vn{u}}^2 + \norm{\Vn{v}}^2-2(\Vn{u} \cdot \Vn{v})&=\norm{\Vn{u}}^2 +
\norm{\Vn{v}}^2 - 2 \norm{\Vn{u}}\norm{\Vn{v}}\cos{\theta}
\shortintertext{simplifying this, we get}
\Vn{u} \cdot \Vn{v} &= \norm{\Vn{u}}\norm{\Vn{v}}\cos{\theta}
\end{align*}
Therefore, we have shown that if $\Vn{u}$ and $\Vn{v} \in \mathbb{R}^3$ are non-zero vectors and
$\theta \in [0,\pi)$ is the angle between them, then
$\norm{\Vn{u} \cdot \Vn{v}} = \norm{\Vn{u}}\norm{\Vn{v}}\cos{\theta}$
\qed}
\item \Que{Let $\Vn{u}$ and $\Vn{v}$ be two sides of a triangle. Find the area of the triangle.}
\Ans{
The area of a triangle is defined as $A = \frac{bh}{2}$
where $b,h \in \left[0, \infty \right)$
are the base length and height of the triangle, respectively.
Let $b = adjacent = \norm{\Vn{u}}$ and $hypotenuse = \norm{\Vn{v}}$.
Using the definition of $\sin{\theta} = \frac{opposite}{hypotenuse}$,
and considering the $h=height = opposite$,
we find that $\sin{\theta} = \frac{h}{\norm{\Vn{v}}}$
and subsequently $h = \norm{\Vn{v}}\sin{\theta}$.
\\~\\ Since $\sin^2{\theta} + \cos^2{\theta}=1$
and $\cos{\theta} = \frac{\Vn{u}\cdot\Vn{v}}{\norm{\Vn{u}}\norm{\Vn{v}}}$
it follows that
\begin{align*}
\sin{\theta} &= \sqrt{1-\left(\frac{\Vn{u}\cdot\Vn{v}}{\norm{\Vn{u}}\norm{\Vn{v}}}\right)^2} \text{ for }\theta \in [0, \pi) \\
&= \frac{1}{\norm{\Vn{u}}\norm{\Vn{v}}}
\sqrt{\norm{\Vn{u}}^2\norm{\Vn{v}}^2-(\Vn{u}\cdot\Vn{v})^2
}\\
&= \frac{1}{\norm{\Vn{u}}\norm{\Vn{v}}}
\sqrt{(u_1^2+u_2^2+u_3^2)(v_1^2+v_2^2+v_3^2)-(u_1v_1+u_2v_2+u_3v_3)(u_1v_1+u_2v_2+u_3v_3)
}\\
&= \frac{1}{\norm{\Vn{u}}\norm{\Vn{v}}}
\sqrt{(u_1^2v_2^2-2u_1v_2u_2v_1+u_2^2v_1^2)+
(u_1^2v_3^2-2u_1v_3u_3v_1+u_3^2v_1^2)+
(u_2^2v_3^2-2u_2v_3u_3v_2+u_3^2v_2^2)
}\\
&= \frac{1}{\norm{\Vn{u}}\norm{\Vn{v}}}
\sqrt{(u_1v_2-u_2v_1)^2+
(u_1v_3-u_3v_1)^2+
(u_2v_3-u_3v_2)^2
}\\
&= \frac{\norm{\Vn{u} \times \Vn{v}}}{\norm{\Vn{u}}\norm{\Vn{v}}}
\end{align*}
and subsequently
\begin{align*}
A = \frac{bh}{2} = \frac{\norm{\Vn{u}}\norm{\Vn{v}}\sin{\theta}}{2}
&= \frac{\norm{\Vn{u}}\norm{\Vn{v}}\norm{\Vn{u}\times\Vn{v}}}
{2\norm{\Vn{u}}\norm{\Vn{v}}}
= \frac{\norm{\Vn{u}\times\Vn{v}}}{2}
\end{align*}
}
\end{enumerate}
\newpage
\item Let $P=(1,4,-3)$, $Q=(5,1,-3)$, and $R=(-1,1,2)$ be points in $\mathbb{R}^3$.
\begin{enumerate}[label=(\alph*)]
\item \Que{Explain how you would write the parametric equation of the line through $X$, where $\Vn{v}$ gives the direction of a line.}
\Ans{
I would take a starting point $X=x_0$ and add $\Vn{v}$ scaled by the parameter $s$ for all $s \in \mathbb{R}$.
% Let $p_0 = X = (x_0, y_0, z_0)$ and $\Vn{v} = \Ve{ x,y,z } $ and
% define line $L = \lbrace p : p = p_0 + t\Vn{v}$ for all $t \in \mathbb{R} \rbrace$
% \begin{align*}
% &L_x(t) = x_0 + tx
% &&L_y(t) = y_0 + ty
% &&&L_z(t) = z_0 + tz
% \end{align*}
}
\item \Que{Find the parametric equation of the lines $\overrightarrow{PQ}, \overrightarrow{PR}, \overrightarrow{QR}$}
\Ans{
Let $\Vn{u} = \overrightarrow{PQ} = \Ve{ 4, -3, 0 }$
and $\Vn{v} = \overrightarrow{PR} = \Ve{ -2,-3, 5 }$
and $\Vn{w} = \overrightarrow{QR} = \Ve{ -6, 0, 5 }$
\begin{align*}
PQ(s) = p_0 + s\Vn{u}
&= (1,4,-3) + s\Ve{ 4,-3,0} \\
PR(s) = p_0 + s\Vn{v}
&= (1,4,-3) + s\Ve{ -2,-3,5 } \\
QR(s) = q_0 + s\Vn{w}
&= (5,1,-3) + s\Ve{-6,0,5}
\end{align*}
for all $s \in \mathbb{R}$
% \begin{align*}
% &PQ_x(t)=1+4t &&PR_x(t)=1-2t &&&QR_x(t)=5-6t\\
% &PQ_y(t)=4-3t &&PR_y(t)=4-3t &&&QR_y(t)=1~~~~~~\\
% &PQ_z(t)=-3 &&PR_z(t)=5t-3 &&&QR_z(t)=5t-3
% \end{align*}
}
\item \Que{Explain why any linear combination of $\overrightarrow{PQ}$ and $\overrightarrow{PR}$ must be in the same plane as $P, Q, R$.}
\Ans{
A linear combination of vectors is the sum of those vectors each multiplied by a corresponding scalar value.
As scaling a vector does not change its direction, any linear combination of two vectors will form a new vector that is co-planar with both original vectors. As long as the two vectors are not co-linear and neither is the zero vector, all possible linear combinations form a plane. If the two are co-linear then they are also co-planar.
}
\item \Que{Use the proceeding idea to write the parametric equation of the plane $PQR$.}
\Ans{
Let $p_0 = P = (1,4,-3)$ be a point on the plane $PQR$,
and let $\Vn{u} = \overrightarrow{PQ} = \Ve{ 4, -3, 0 }$
and $\Vn{v} = \overrightarrow{PR} = \Ve{ -2,-3, 5 }$
be vectors on the plane $PQR$.
\begin{align*}
PQR(s,t) &= \lbrace p:p=p_0+s\Vn{u}+t\Vn{v} \text{ for all } s,t \in \mathbb{R}\rbrace
= (1,4,-3) + s\Ve{4,-3,0} + t\Ve{-2,-3,5}
\end{align*}
}
\item \Que{Find the area of the triangle $\Delta PQR$.}
\Ans{
Let $\Vn{u} = \overrightarrow{PQ} = \Ve{ 4,-3,0}$
and $\Vn{v} = \overrightarrow{PR} = \Ve{ -2,-3, 5 }$
be vectors in $\mathbb{R}^3$ forming two sides of $\Delta PQR$.
\begin{align*}
area(\Delta PQR) &= \frac{\norm{\Vn{u}\times\Vn{v}}}{2}\\
&= \frac{1}{2}\sqrt{[(4)(-3) - (-3)(-2)]^2+[(4)(5)-(0)(-2)]^2 + [(-3)(5)-(0)(-3)]^2}\\
&= \frac{1}{2}\sqrt{(-18)^2 + (20)^2 + (-15)^2}
= \frac{\sqrt{949}}{2}
\approx \underline{15.403}
\end{align*}
}
\item \Que{Find the distance between the point $R$ and the line $\overrightarrow{PQ}$.}
\Ans{
Let $\Vn{u} = \overrightarrow{PQ} = \Ve{ 4,-3,0}$
and $\Vn{v} = \overrightarrow{PR} = \Ve{ -2,-3, 5 }$
be vectors in $\mathbb{R}^3$, and let $\theta \in [0,\pi)$ be the angle between them.
The distance between $R$ and $\overrightarrow{PQ}$ is equivalent
to the triangle height that we calculated in question 2(b) above, that is:
\begin{align*}
dist(R, \overrightarrow{PQ}) &= \norm{\Vn{v}}\sin{\theta}
= \frac{\norm{\Vn{v}}\norm{\Vn{u}\times\Vn{v}}}{\norm{\Vn{u}}\norm{\Vn{v}}}
= \frac{\norm{\Vn{u}\times\Vn{v}}}{\norm{\Vn{u}}}\\
&= \frac{\sqrt{[(4)(-3) - (-3)(-2)]^2+[(4)(5)-(0)(-2)]^2 + [(-3)(5)-(0)(-3)]^2}}
{\sqrt{4^2+(-3)^2+0^2}}\\
&= \frac{\sqrt{949}}{5}
\approx \underline{6.161}
\end{align*}
}
\end{enumerate}
\newpage
\item Suppose $M$ is the coefficient matrix for a system of equations augmented by the constants of the equation. For each of the following, identify the corresponding operation on a system of equations; then state whether the operation is allowable or forbidden. Assume $c \not = 0$.
\begin{enumerate}[label=(\alph*)]
\item \Que{Multiplying every term of a row by $c$.}
\Ans{
Multiplying every term in a row by a scalar would not result in a change of direction of the underlying vector of that row, and thus would have no effect on the system as a whole. Thus this is \underline{allowed}.
}
\item \Que{Switching two columns.}
\Ans{
Switching two columns results in a switching of coefficients between variables, resulting in a possibly different value for the system. Thus this operation is \underline{forbidden}.
}
\item \Que{Switching two rows.}
\Ans{
Switching two rows results in a null operation on the system, as each row represents a discrete equation in the system, and there is no defined ordering of the equations in the system. Therefore this operation is \underline{allowed}.
}
\item \Que{Adding $c$ to each term in a row.}
\Ans{
Adding a constant to all terms in a row would result in a different value for the equation, for example
\begin{align*}
3x&=15\\
x&=5
\shortintertext{is not equivalent to}
5x&=17\\
x&\approx 3.4
\end{align*}
Therefore this operation is \underline{forbidden}.
}
\item \Que{Multiplying every term in a row by $c$, then adding the corresponding terms to another row.}
\Ans{
If we were to conceptualize the equations of a system of linear of equations as being co-planar, any linear combination of equations in the system would form a new equation that is co-planar with the existing equations, and thus is readily acceptable as a new equation in the system. Therefore this operation is \underline{allowed}.
}
\item \Que{Suppose that, after applying a sequence of allowable operations to $M$, you end up with a row consisting of all zeroes except the last entry, which is non-zero. What does this say about the original system of equations?}
\Ans{If by "last entry" you mean the augmented column, then you have a system of equations with no viable solutions, as there is no way that a combination of variables all scaled by zero can equal a non-zero value.
}
\end{enumerate}
\newpage
\item Find a parameterization of the following systems of equations.
\begin{enumerate}[label=(\alph*)]
\item \Que{
\begin{minipage}[t]{0.25\textwidth}
\begin{flushright}
$3x+2y=5$
\end{flushright}
\end{minipage}
}
\Ans{
Let $x=1+2s$, \\
Then:
\begin{align*}
3(1+2s) + 2y &= 5 &&\rightarrow 2y = 5-(3+6s) &&&\rightarrow
y =\frac{2-6s}{2}&&&&\rightarrow y=1-3s
\end{align*}
Thus $(x,y) = (1,1) + s\Ve{2,-3}$\ for all $s \in \mathbb{R}$
}
\item \Que{
\begin{minipage}[t]{0.25\textwidth}
\begin{flushright}
$3w-2x-4y+2z=0$\par $3x+2y-5z=0$\par $2y-1z=0$
\end{flushright}
\end{minipage}
}
\Ans{
Let $z=18s$. \\
Then:
\begin{align*}
2y - 18s &= 0 &&\rightarrow 2y = 18s &&&\rightarrow y = 9s \\
3x +2(9s) - 5(18s) &= 0 &&\rightarrow 3x = 72s &&&\rightarrow x = 24s\\
3w-2(24s)-4(9s)+2(18s) &=0 &&\rightarrow 3w = 48s &&&\rightarrow w = 16s
\end{align*}
Thus $(w,x,y,z) = (0,0,0,0) + s\Ve{16,24,9,18}$\ for all $s \in \mathbb{R}$
}
\item \Que{
\begin{minipage}[t]{0.25\textwidth}
\begin{flushright}
$2w+3x-5y-2z=0$\par $x+2y-1z=0$
\end{flushright}
\end{minipage}
}
\Ans{
Let $z=4s$, \\ and $x=4t$. \\ Then:
\begin{align*}
4t+2y-4s&=0 &&\rightarrow 2y=4s-4t &&&\rightarrow y=2s-2t \\
2w+3(4t)-5(2s-2t)-2(4s)&=0 &&\rightarrow 2w=18s-22t &&&\rightarrow w=9s-11t
\end{align*}
Thus $(w,x,y,z) = (0,0,0,0) + s\Ve{9,0,2,4} + t\Ve{-11,4,-2,0}$ for all $s,t \in \mathbb{R}$.
}
\end{enumerate}
\end{enumerate}
\end{document}